The Origins of Capitalism and the "Rise of the West" - Mielants, Eric H (Temple University Press, 2007)
In this study, Eric Mielants provides a novel interdisciplinary interpretation of the origins of modernity and capitalism in particular. He argues that contrary to popular thinking, the Rise of the West should not be analyzed in terms of the Industrial Revolution or the colonization of the New World, but viewed from long-term developments that occurred in the Middle Ages. A fascinating overview of different civilizations in East Asia, South Asia, and Northwestern Africa is provided and systematically compared and contrasted with Western Europe. This book addresses some of the major debates that have recently unfolded in world history, comparative sociology, political economy, sociological theory and historical sociology. Mielants indicates how many existing theories (such as Marxism, World-Systems Theory and Smithian Modernization Theory) have suffered from either Eurocentric or limited temporal and spatial analyses, which prevents them from a complete understanding of why the origins of capitalism and citizenship emerged in Western Europe.